LITERASI MEDIA, UPAYA CERDAS DALAM MENGKONSUMSI TAYANGAN TELEVISI - Amelia, Citra Ratna (Capture : Jurnal Seni Media Rekam, 2015)
The development of the mass media or broadcasting of terrestrial television in Indonesia is very rapid. Increasing number of terrestrial television stations in Indonesia makes the competition among television stations increasingly stringent. The terrestrial television requires a relatively high amount of revenue for operational costs. Advertising is one source of revenue. The advertisers will pair its ads in the program of interest by the public. Therefore, the television station competely to create programs that liked by the public. This is done so that the televison station can fight the competition. To determine whether the programs are interesting for public or not , the TV station uses the services of AGB Nielsen to measure whoever are viewing terrestrial television. The results of AGB Nielsen survey are rated and shared. The result of rating and share of the programs are liked by the public interest or not become a benchmark. The higher the rating and share program means the higher the interest of the public to watch the program. That became a problem and interesting to be discussed, in which in reality many programs are reprimanded by the KPI (Indonesian Broadcasting Commission) even in fact they have a high ratings. Whereas the program that gets a reprimand from the KPI is a program that can be said to be problematic and it cannot be imagined what happen if the problematic program maintained by the television station is on the pretext of a high rating. Facing this kind of television, viewers required to be more selective and critical of television, because media owner of television defends its economic interests. Therefore, the audience should have the skills of media literacy. Ability to digest what ispresented by the mass media, then the television is very important.Keywords:Media literacy, rating, share, AGB Nielsen